The Effect Of Giving Banana Stem Compos With EM4 Concentration Variation And Urea Fertilizer On The Growth Of : PENGARUH PEMBERIAN KOMPOS BATANG PISANG DENGAN VARIASI KONSENTRASI EM4 DAN PUPUK UREA TERHADAP PERTUMBUHAN STEK LADA (Piper nigrum L.) VARIETAS MALONAN 1 - Fredrick Ngo; rustam baraq noor (Agrifarm : Jurnal Ilmu Pertanian, 2021)
This research was conducted at the Experimental Garden of Widya Gama Mahakam University Samarinda, Faculty of Agriculture, Jalan KH. Wahid Hasyim. The study was conducted in January - April 2020. This study used a factorial randomized block design (RBD) with 2 treatment factors and 3 replications. The first factor was the application of banana stem compost with various concentrations of EM4 consisting of 4 levels, namely P0 = banana stem compost without EM4, P1 = banana stem compost with EM4 concentration of 50 ml L-1 water, P2 = banana stem compost with EM4 concentration of 75 ml. L-1 water, P3 = banana stem compost with a concentration of EM4 100 ml L-1 water and the second factor is the dose of urea fertilizer which consists of 4 levels, namely, D0 = control, D1 = 1 g urea / polybag, D2 = 2 g urea / polybag, D3 = 3 g urea / polybag. The results of the research giving banana stem compost with variations in the concentration of EM4 and the dose of urea fertilizer and the interaction of the two treatments had a very significant effect on plant height at the age of 20, 40, 60 and 80 DAS, with the best treatment P3 = 28.67 cm, D3 = 28, 21 cm and P3D3 = 32.33 cm, then had a very significant effect on the number of shoots at the age of 60 and 80 DAS with the best treatment P3 = 6.67 fruit, D3 = 6.17 fruit and P3D3 = 8.33 fruit, and very influential significant on the number of leaves at the age of 40, 60 and 80 DAS with the best treatment P3 = 8.58 strands, D3 = 8.83 strands and P3D2 = 10.67 strands.